Enthusiasm and Participation in Arabic Language Learning: A Qualitative Case Study in an Islamic Primary School Based on Curran’s Theory - Lutfiya Naillul Muna; Inayah, Inayah; Zulaikha, Zulaikha; Mufidah, Mufidah (IAIN Madura, 2026)
This study identifies problems in Arabic language learning by examining student enthusiasm, participation and influencing factors. Using qualitative case explanatory field research, data wre collected through observation, interviews, and open-ended questionnaires from fifth grade students of the Islamic Special Program (Takhasus) at Madrasah Ibtida’iyah (MI) Taufiqiyah Semarang. The findings indicated that low enthusiasm and participation are influenced by limited learning motivation, insufficient teacher resources, perceptions of Arabic as a difficult subject, and limited instructional variation. These findings align with Charles Curran's theory, which emphasizes emotional support and a sense of security in learning. The use of interactive strategies such as educational games, group discussion, quizzes, and reward programs, was found to increase student engagement and interest. This study contributes theoretically and practically by enriching the literature and providing evidence-based insights for instructional practices in Islamic elementary education, and recommends further quantitative or mixed-method research.